The Relationship of Appetite and Emesis to Weight Gain Pregnancy - Erowati, Dewi; Marlina, Yessi; Paramita, Irma Susan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
In general, 70-80% of pregnant women experience emesis or nausea and vomiting which decreased appetite and nutritional intake of pregnant women. Whereas nutrition really contributes to the growth and development of the fetus, children after birth to adulthood. Pregnant women who are thin and gain less weight during pregnancy will increase the risk of giving birth to babies with low birth weight (LBW). This study aims to analyze the relationship between appetite and emesis to the weight gain of pregnant women. This research is a cross sectional study conducted in Pekanbaru City. The research respondent were 91 pregnant women who met the inclusion criteria, namely pregnant women who had a record of early pregnancy weight in the KIA book. Measurement of appetite and emesis using a modified questionnaire from the Simplified Nutrition Appetite Questionnaire (SNAQ) and Pregnancy-Unique Quantification of Emesis (PUQE-24) Scale which was carried out online related to the 2020 COVID-19 pandemic. The results showed that there was a relationship between appetite and weight gain in the 1st trimester of pregnancy. While there was no relationship between emesis and weight gain. This is because the average respondent of pregnant women does not experience appetite and emesis which are at risk. In addition, the gestational age of 62.6% of respondents, namely at the age of the third trimester, tended to have improved appetite and did not experience emesis. In addition, there has also been an increase in weight gain.